Dislocation interactions and crack nucleation in a fatigued near-alpha titanium alloy. (November 2018) - Joseph, S.; Lindley, T.C.; Dye, D.
Abstract: Dislocation interactions at the crack nucleation site were investigated in near-alpha titanium alloy Ti-6242Si subjected to low cycle fatigue. Cyclic plastic strain in the alloy resulted in dislocation pile-ups in the primary alpha grains, nucleated at the boundaries between the primary alpha and the two-phase regions. These two phase regions provided a barrier to slip transfer between primary alpha grains. We suggest that crack nucleation occurred near the basal plane of primary alpha grains by the subsurface double-ended pile-up mechanism first conceived by Tanaka and Mura. Superjogs on the basal 〈 a 〉 dislocations were observed near the crack nucleation location. The two phase regions showed direct transmission of a 3 dislocations between secondary alpha plates, transmitted through the beta ligaments as a [ 010 ], which then decompose into ( a / 2 ) 〈 111 〉 dislocation networks in the beta. The beta ligaments themselves do not appear to form an especially impenetrable barrier to slip, in agreement with the micropillar and crystal plasticity investigations of Zhang et al. Graphical abstract: Highlights: Dislocations below a low cycle fatigue crack initiation site in near-alpha Ti6242Si were investigated. Dislocation pile-ups were observed, transferring easily between primary alpha grains. Two phase alpha+beta regions showed direct transmission of a3 dislocations through the beta ligaments. A subsurface double-ended pile-up in αp caused crack nucleation, consistent with the mechanism proposed by Tanaka and Mura. The initiating facet was near-basal, the misorientation being associated with superjog basal dislocations.